(E)‐3‐X‐indoline‐2‐ones as potent and selective inhibitors against different receptor tyrosine kinase (RTKs) in solution vs gas phase, at DFT. (2nd January 2019) - Soleimani‐Amiri, S.; Koohi, M.
Abstract: Using DFT SCRF calculations, we have evaluated the solvent effects on the structure, stability, and electronic properties of biologically active compounds as ( E )‐3‐X‐indoline‐2‐one derivatives (X = phenyl, furan‐2‐yl, 1H‐pyrrol‐2‐yl, and thiophen‐2‐yl, I‐IV, respectively) in six solvents. These solvents differ in their polarity with the dielectric constants varying from 2.2 to 78.5 including benzene, C2 H4 Cl2, EtOH, H2 O, nitromethane, and DMSO. Moreover, two of them have a hydrogen‐bond donor character. All possible hydrogen‐bonding in the water solution with oxygen and nitrogen atoms as hydrogen‐acceptor centers in indoline‐2‐ones derivatives, I‐IV, have been considered in our studies. The stability of each solute (I ‐IV ) depends on the dielectric constant of the solvent and the possibility of the hydrogen bonding. Moreover, the highest observed solvent‐gas phase energy gaps (∆ E s‐g ) relate to structureIII in water, whereas the lowest ∆ E s‐g is associated withII in benzene. Thus, III is the most solvent sensitive and enjoys maximum stabilization in water. On the other extreme, II is the least solvent sensitive, and its stability is the least affected by salvation in benzene. Forbidden concerted [1, 6] and [1, 3]‐H shift mechanisms are suggested for the ketoneIII ―III′, III′′ enole tautomerizations in gas phase, while allowed step‐by‐step [1, 6] and [1, 3]‐H shifts are proposed for tautomerization in water. Abstract : A flow chart for examination of solvent effects on biologically active (I ‐IV ) are probed, at DFT (for a: total energy difference (∆ E s‐g ) between solvent (s) and gas (g) phases, b: dipole moment (μ), c: symmetry, d: structural parameters, e: band gap (∆ E LUMO‐HOMO ), f: nucleophilicity indexes ( N ), g: global electrophilicities ( ω ), and h: NICS (0, 0.5, and 1).